Mampukah Kebijakan Dividen Memoderasi Kinerja ESG, Profitabilitas, dan Struktur Modal terhadap Nilai Perusahaan? - Lusmeida, Herlina; Sudardja, Cheryl (E-Jurnal Akuntansi; Vol 34 No 3 (2024)DO - 10.24843/EJA.2024.v34.i03.p06, 2024)
Financial factors and non-financial factors currently influence company value. This research also wants to look at the role of Dividend Policy in the relationship between ESG Performance, Profitability and Capital Structure with Company Value. This research uses non-financial sector companies that have been listed on the Indonesia Stock Exchange, Singapore Exchange, Bursa Malaysia and Thailand Stock Exchange for the 2019-2022 period with a total of 103 companies as samples. The analysis technique used is multiple linear regression. The research results obtained show that ESG Performance, Profitability, Capital Structure and Dividend Policy are positively correlated with Company Value. Dividend policy strengthens the relationship between Profitability and Company Value, but Dividend Policy cannot moderate the relationship between ESG Performance and Capital Structure and Company Value. Keywords: Firm Value; ESG Performance; Profitability; Capital Structure; Dividend Policy